Uji Preferensi Terhadap Produk Abon Sukun (Artocarpus altilis) Berdasarkan Atribut Sensoris - Desita Jumiar, Alfath; Pratomo Sibuea, Budi; Rabbani, Fikri (Politeknik Negeri Ketapang, 2023)
Shredded food is a type of dry food with a distinctive shape whose processing is done by boiling, shredding, mixing spices, frying and pressing. The basic ingredients for shredded meat are not only sourced from animal fiber, but can also be sourced from vegetable fiber, one of which is breadfruit. Young breadfruit has enough fiber content that it meets the requirements for making vegetable shredded meat. This research aims to determine the level of panelists preference for breadfruit floss. Making shredded breadfruit is done using two treatments, namely shredded breadfruit with coconut milk and without coconut milk. Preference testing uses a hedonic test, with 30 panelis. The test result showed that the panelists tended to slightly prefer shredded breadfruit with coconut milk based on aroma, taste, and texture parameters with value respectively 6,43, 6,33, and 6,77, while shredded breadfruit without coconut milk obtained a neutral preference based on aroma, taste, and texture parameters with values respectively 5,97, 5,67, and 5,90. The yield of shredded breadfruit with coconut milk treatment was 51,2% higher than the treatment without coconut milk.